2022
DOI: 10.3390/cancers14020348
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Regulation of ERK5 Expression and Function in Cancer

Abstract: Extracellular signal-regulated kinase 5 (ERK5) is a unique kinase among MAPKs family members, given its large structure characterized by the presence of a unique C-terminal domain. Despite increasing data demonstrating the relevance of the ERK5 pathway in the growth, survival, and differentiation of normal cells, ERK5 has recently attracted the attention of several research groups given its relevance in inflammatory disorders and cancer. Accumulating evidence reported its role in tumor initiation and progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 190 publications
1
24
1
Order By: Relevance
“…This effectively reduces ERK5 mRNA and protein between 30% and 70% in the different cell types used in this study [8,14,16], which we confirmed below in this study (see Figure 4E). As previously described, ERK5 has multiple functions, e.g., adaptor, transcriptional activator, kinase and differences on ERK5 levels can differently modulate its effects on the expression of its targets [17][18][19][20][21]. These decreases in expression were similar for MEF2 proteins, although the decrease was bigger for MEF2A than for MEF2C [8,14,16].…”
Section: Changes In Metabolism Regulate Expression Of Proteins Involv...supporting
confidence: 51%
See 2 more Smart Citations
“…This effectively reduces ERK5 mRNA and protein between 30% and 70% in the different cell types used in this study [8,14,16], which we confirmed below in this study (see Figure 4E). As previously described, ERK5 has multiple functions, e.g., adaptor, transcriptional activator, kinase and differences on ERK5 levels can differently modulate its effects on the expression of its targets [17][18][19][20][21]. These decreases in expression were similar for MEF2 proteins, although the decrease was bigger for MEF2A than for MEF2C [8,14,16].…”
Section: Changes In Metabolism Regulate Expression Of Proteins Involv...supporting
confidence: 51%
“…Other physiological effects of DCA are mediated by ERK5, also mainly through MEF2 activation [15,16]. Although ERK5 also has its own transcriptional domain, it translates stress signals, including metabolic stress, to gene expression through MEF2 [17][18][19][20][21]. ERK5 plays key roles multiple cellular functions [20], including on cell metabolism [22] and to some extent in the control of lipid metabolism [8,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, from a clinical point of view, our murine model opens a new window of therapeutic and diagnostic possibilities for sarcomatous pathologies based on ERK5-dependent signaling [ 24 ]. In this regard, the effectivity of ERK5 inhibitors in preclinical models has been shown [ 49 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, ERK5, one of the canonical members of MAPKs superfamily described more than 25 years ago [ 20 , 21 ], is highly expressed in sarcomatous pathology, as indicated in The Cancer Genome Atlas (TCGA) series (see below). Interestingly, this particular MAPK signaling pathway has been linked to cancer [ 22 , 23 ], and it is expected to exploit its clinical implications in the coming years [ 24 ]. Indeed, ERK5 has been related to several types of tumors such as breast [ 25 ], multiple myeloma [ 26 ], or cholangiocarcinoma [ 27 ].…”
Section: Introductionmentioning
confidence: 99%